2019
DOI: 10.1029/2019gl086133
|View full text |Cite
|
Sign up to set email alerts
|

A Cautionary Note on the Long‐term Trend in Activity of the Madden‐Julian Oscillation During the Past Decades

Abstract: Recent studies suggest that frequency of active phases of the Madden-Julian Oscillation (MJO) over the Maritime Continent and western Pacific, that is, the MJO Phases 4-6 defined by the real-time multivariate MJO (RMM) index, has increased in recent winters. A robust positive trend in MJO Phase 4-6 days during 1979-2015 winters is confirmed in this study. Our analyses, however, suggest that this trend could be exaggerated due to the blended low-frequency variability signals in the RMM. When the winter RMM is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…(2019) employed the yearly time series of residence time of the MJO, to illustrate that the warming trend of SST over the Western Pacific can enhance the major MJO convection over the Maritime Continent. Our results confirm such a link through the daily time series of Kelvin wave and OLR, moreover the conclusions avoid involving the large uncertainties in computing the residence time of the MJO (Lyu et al., 2019).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…(2019) employed the yearly time series of residence time of the MJO, to illustrate that the warming trend of SST over the Western Pacific can enhance the major MJO convection over the Maritime Continent. Our results confirm such a link through the daily time series of Kelvin wave and OLR, moreover the conclusions avoid involving the large uncertainties in computing the residence time of the MJO (Lyu et al., 2019).…”
Section: Resultssupporting
confidence: 84%
“…Here, we aim to understand whether the Kelvin wave components and SST play roles in the recent change of the MJO. It has been reported that the estimated values of the MJO residence time over the Maritime Continent were not robust when using different filtering methods of the real‐time multivariate MJO (RMM, Wheeler & Hendon, 2004) indices, which might disturb the diagnosis of the MJO change (Lyu et al., 2019). While it cannot be determined which method for deriving the residence time is accurate, therefore it is also necessary to recheck the changes of the MJO through another perspective.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed daily anomalies of OLR and 850-hPa zonal wind (U850) are obtained by removing the slow annual cycle (annual mean and the first three annual harmonics of the 15-year average) and interannual variability (average of the previous 120 days). This processing method is mostly used for the verification of real-time intraseasonal forecast, although it may be limited in filtering out the interannual and long-term variability (Lyu et al 2019a). For the results from the S2S hindcast, EXP1, and EXP2, the daily anomalies are defined by removing the lead-dependent model climatology and the mean of anomalies over the previous 120 days.…”
Section: Model and Datamentioning
confidence: 99%